Olanzapine-induced leucopaenia and thrombocytopaenia in an elderly patient: a case report and review of the evidence - Malik, Yogender Kumar (Gen Psychiatr, 2018)
Haematological adverse effects of antipsychotics are rare but life threatening. Existing literature is limited to case reports, which are mostly reported on second generation antipsychotics (clozapine, olanzapine, risperidone, quetiapine). Elderly individuals are at risk of developing side effects with any psychotropics. Olanzapine is commonly used for the management of psychotic symptoms as well as for the management of behavioural and psychological problems with dementia in the elderly. In this case report, we report thrombocytopaenia and leucopaenia in an elderly individual with schizophrenia which developed after initiation of olanzapine and reverted back after stoppage of the drug. This case report highlights that the elderly are susceptible to develop haematological side effects with olanzapine and hence monitoring may be essential.